GREEN HUMAN RESOURCE MANAGEMENT, GREEN INNOVATION, DAN SUSTAINABLE PERFORMANCE DALAM PERSPEKTIF MANAJEMEN BERKELANJUTAN: SEBUAH LITERATURE REVIEW - Sarida Sirait; Mutia Nurhalizah; Abdul Rahim Siregar; Jufrizen; Siti Mujiatun (Smart Education, 2026)
Abstract: The development of sustainability issues has encouraged organizations to integrate economic, social, and environmental aspects into their business strategies. Green Human Resource Management (GHRM) has emerged as a strategic approach that integrates human resource management practices with an organization's environmental goals. Green Innovation, on the other hand, has become a crucial tool in producing more environmentally friendly products and processes, while Sustainable Performance is an indicator of an organization's success in achieving long-term sustainability. This article aims to conduct a literature review on the relationship between Green Human Resource Management, Green Innovation, and Sustainable Performance from a sustainable management perspective. The study's findings indicate that GHRM practices play a role in building employee green competencies and behaviors, which in turn drive Green Innovation. Green Innovation has been shown to be a mediating mechanism that strengthens the influence of GHRM on Sustainable Performance. Therefore, the integration of GHRM and Green Innovation is a crucial strategy for enhancing organizational competitiveness and sustainability. Keywords: Green Human Resource Management, Green Innovation, Sustainable Performance, Sustainability, Sustainable Management. Abstrak: Perkembangan isu keberlanjutan telah mendorong organisasi untuk mengintegrasikan aspek ekonomi, sosial, dan lingkungan ke dalam strategi bisnis. Green Human Resource Management (GHRM) muncul sebagai pendekatan strategis yang mengintegrasikan praktik manajemen sumber daya manusia dengan tujuan lingkungan organisasi. Di sisi lain, Green Innovation menjadi instrumen penting dalam menghasilkan produk dan proses yang lebih ramah lingkungan, sedangkan Sustainable Performance merupakan indikator keberhasilan organisasi dalam mencapai keberlanjutan jangka panjang. Artikel ini bertujuan melakukan kajian literatur mengenai hubungan antara Green Human Resource Management, Green Innovation, dan Sustainable Performance dalam perspektif manajemen berkelanjutan. Hasil kajian menunjukkan bahwa praktik GHRM berperan dalam membangun kompetensi dan perilaku hijau karyawan yang selanjutnya mendorong Green Innovation. Green Innovation terbukti menjadi mekanisme mediasi yang memperkuat pengaruh GHRM terhadap Sustainable Performance. Dengan demikian, integrasi GHRM dan Green Innovation menjadi strategi penting dalam meningkatkan daya saing dan keberlanjutan organisasi. Kata Kunci: Green Human Resource Management, Green Innovation, Sustainable Performance, Sustainability, Manajemen Berkelanjutan